2018
DOI: 10.1038/s41598-018-27455-5
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of squalene by singlet oxygen and free radicals results in different compositions of squalene monohydroperoxide isomers

Abstract: Oxidation of squalene (SQ) causes a decline in the nutritional value of SQ in foods, as well as an accumulation of SQ oxidation products in skin lipids which lead to adverse skin conditions. However, mechanistic insights as to how SQ is oxidized by different oxidation mechanisms have been limited, and thus effective measures towards the prevention of SQ oxidation have not been identified. In this study, we oxidized SQ by either singlet oxygen oxidation or free radical oxidation, and monitored the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 39 publications
1
44
0
1
Order By: Relevance
“…The following multiple reaction monitoring (MRM) pairs were utilized for the analysis of each SQOOH isomer: m/z 465.4 > 433.5, 2‐OOH‐SQ; m/z 465.4 > 395.3, 3‐OOH‐SQ; m/z 465.4 > 365.3, 6‐OOH‐SQ; m/z 465.4 > 297.2, 10‐OOH‐SQ; m/z 465.4 > 181.1, 7‐OOH‐SQ; m/z 465.4 > 229.2, 11‐OOH‐SQ. Other MS parameters, consistent with our previous study, were as follows: curtain gas, 30.0 psi; collision gas, 7.0 psi; ion spray voltage, 5500.0 V; temperature, 400.0 °C; ion source gas 1, 80.0 psi; and ion source gas 2, 60.0 psi. External calibration curves for quantitation were prepared with the use of synthetic SQOOH isomer standards.…”
Section: Methodssupporting
confidence: 57%
See 3 more Smart Citations
“…The following multiple reaction monitoring (MRM) pairs were utilized for the analysis of each SQOOH isomer: m/z 465.4 > 433.5, 2‐OOH‐SQ; m/z 465.4 > 395.3, 3‐OOH‐SQ; m/z 465.4 > 365.3, 6‐OOH‐SQ; m/z 465.4 > 297.2, 10‐OOH‐SQ; m/z 465.4 > 181.1, 7‐OOH‐SQ; m/z 465.4 > 229.2, 11‐OOH‐SQ. Other MS parameters, consistent with our previous study, were as follows: curtain gas, 30.0 psi; collision gas, 7.0 psi; ion spray voltage, 5500.0 V; temperature, 400.0 °C; ion source gas 1, 80.0 psi; and ion source gas 2, 60.0 psi. External calibration curves for quantitation were prepared with the use of synthetic SQOOH isomer standards.…”
Section: Methodssupporting
confidence: 57%
“…Singlet oxygen and free radical oxidation of squalene were performed according to a previous report . For singlet oxygen oxidation, 100 µg of squalene was dissolved in 50 µL of ethanol/chloroform (1:1, v/v), to which 50 µL of a 20 mM EP solution in ethanol/chloroform (1:1, v/v) was added and incubated at 20 °C for 4 hours.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, squalene has been shown to oxidize at lower temperatures than cholesterol. Specifically, Shimizu et al found that oxidation of squalene by heating is observed after incubation at 40, 50, and 60°C for 8 h. Frankel et al . also demonstrated the process of peroxide formation from squalene at 40 and 60 °C.…”
mentioning
confidence: 99%